Alternance and Financial Efficiency A Municipal Analysis In Hidalgo, Mexico (2005-2020) (Revista Iberoamericana de Estudios Municipales, 2022)
This article examines the empirical links between party alternation and financial efficiency in the last five municipal elections in Hidalgo (2005-2020). Methodologically, a logistic regression model was estimated with panel data –fixed effects- that calculate the probability of party alternation. The independent variables used are the municipal efficiency of the outgoing government, electoral participation, the competitiveness of past elections and the improvement in coverage of public services. The findings suggest the presence of a possible negative causal association between alternation and performance (the social investment-current expenditure relationship in the year prior to the election). The results also indicate that the electoral participation continues to be important referent for the arrival of a new party to the exercise of municipal administration.
Keywords: political alternation; municipal performance; electoral behavior; municipal studies